Marine Viruses 2016 - Mathias Middelboe (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The research effort, publication rate and scientific community within the field of marine viruses have been growing rapidly over the past decade and viruses are now known to play key roles in microbial population dynamics, diversity and evolution as well as biogeochemical cycling. The compilation of papers included in the current Special Issue highlights the exploration of eukaryotic and prokaryotic viruses, from discovery to complex interplays between virus and host and virus-host interactions with ecologically relevant environmental variables. The discovery of novel viruses and new mechanisms underlying virus distribution and diversity exemplify the fascinating world of marine viruses. The oceans greatly shape Earth's climate, hold 1.37 billion km3 of seawater, produce half of the oxygen in the atmosphere, and are integral to all known life. In a time where life in the oceans is under increasing threat (global warming, pollution, economic use) it is pressing to understand how viruses affect host population dynamics, biodiversity, biogeochemical cycling and ecosystem efficiency.